Association of sTREM‐1 and Neutrophil-to-Lymphocyte Ratio as Prognostic Markers in COVID-19 Short- and Long-Term Mortality - Turgunova L; Mekhantseva I; Akhmaltdinova L; Kostinov M; Zhumadilova Z; Turmukhambetova A (Dove Medical Press, 2023)
Lyudmila Turgunova,1 Irina Mekhantseva,1 Lyudmila Akhmaltdinova,1 Mikhail Kostinov,2,3 Zhibek Zhumadilova,1 Anar Turmukhambetova1 1Karaganda Medical University, Department of Internal Medicine, Karaganda, Kazakhstan; 2I.I. Mechnikov Research Institute of Vaccines and Sera, Moscow, Russia; 3Sechenov First Moscow State Medical University, Department of Epidemiology and Modern Vaccination Technologies, Moscow, RussiaCorrespondence: Irina Mekhantseva, Email Mehanceva@qmu.kzAim: Current problem related to COVID-19 is various complications after disease, especially long-term mortality after COVID-19. Routine blood tests presented their effectiveness in the diagnosis, prognosis and mortality of COVID-19. The neutrophil-to-lymphocyte ratio (NLR) is an important marker of systemic inflammation. Soluble Trigger receptor expressed on myeloid cells-1 (sTREM-1) is considered an intrinsic enhancer of inflammatory signals. This study examined the predictive value of these markers in COVID-19 mortality.Methods: A prospective study was conducted involving patients with COVID-19 in Karaganda, Kazakhstan. The neutrophil-to-lymphocyte ratio (NLR) was calculated as the absolute number of neutrophils divided by the absolute number of lymphocytes. The level of sTREM-1 in the blood serum was evaluated by ELISA.Results: Plasma sTREM-1 concentration greater than 59.08 pg/mL and an NLR greater than 2.29 had an increased risk of early mortality (hazard ratio = 8.07; 95% CI: 1.03- 62.17 and 9.24; 95% CI: 1.202- 71.08, respectively); for long-term mortality of sTREM-1 greater than 47.34 pg/mL (hazard ratio = 7.96; 95% CI: 1.072- 59.18) and NLR greater than 2.10 (hazard ratio = 11.52; 95% CI: 1.551- 85.52).Conclusion: This study suggests that early levels of sTREM-1 and NLR are associated with the risk of 6-month mortality after experiencing COVID-19.Keywords: COVID-19, mortality, neutrophil-to-lymphocyte ratio, sTREM‐1, prognostic markers